The Use of Web-Based Portfolio as Alternatife Assesment in Biology Learning - Saragih, Wilhelminari Br; Sihombing, Natalia; Sitanggang, Jesika; Diansyah, Dedi (Universitas Sembilanbelas November Kolaka, 2021)
The current state of the Covid-19 pandemic has had an impact on various ongoing activities, including learning activities. Currently, the government provides a policy to organize learning from home, known as Learning From Home (BDR). Learning From Home in its implementation requires the support of mobile devices. It is a challenge for both teachers and students to master technology in learning in these conditions. In addition, teachers must also be able to carry out the teaching and learning process or provide assessments/evaluations to students face-to-face (done online). The research objective is to determine the use of alternative assessment-based portfolios in biology learning. The authors want to introduce web-based portfolios as alternative assessments in biology learning in this study. Alternative assessments can support students to understand biology lessons with the task of making lab reports, making herbariums, drawing, writing widespread scientific reports, etc. These are collected in the form of website links. The research method used is a literature study that the author has carried out. The results obtained are using a web-based portfolio as an alternative assessment in biology learning, which is still not widely applied even though this assessment is very efficient to apply in biology learning during the Covid-19 pandemic. This research concludes that every lesson that has been carried out certainly needs to be assessed on student learning outcomes in following each lesson that has been followed. In this case, an alternative web-based portfolio assessment is one of the solutions to evaluate the performance and work of students so that all activities carried out can be rewarded with value. Keywords: Biology Alternative Assessment, Web Based Portofolio